PCSK9 Modulates Macrophage Polarization-Mediated Ventricular Remodeling after Myocardial Infarction - Feifei Wang; Min Li; Aidong Zhang; Hairui Li; Can Jiang; Jun Guo (Journal of Immunology Research)
Background and Aims. An increasing number of high-risk patients with coronary heart disease (similar to acute myocardial infarction (AMI)) are using PCSK9 inhibitors. However, whether PCSK9 affects myocardial repair and the molecular mechanism of PCSK9 modulation of immune inflammation after AMI are not known. The present research investigated the role of PCSK9 in the immunomodulation of macrophages after AMI and provided evidence for the clinical application of PCSK9 inhibitors after AMI to improve cardiac repair. Methods and Results. Wild-type C57BL6/J (WT) and PCSK9-/- mouse hearts were subjected to left anterior descending (LAD) coronary artery occlusion to establish an AMI model. Correlation analysis showed that higher PCSK9 expression indicated worse cardiac function after AMI, and PCSK9 knockout reduced infarct size, improved cardiac function, and attenuated inflammatory cell infiltration compared to WT mice. Notably, the curative effects of PCSK9 inhibition were abolished after the systemic depletion of macrophages using clodronate liposomes. PCSK9 showed a regulatory effect on macrophage polarization in vivo and in vitro. Our studies also revealed that activation of the TLR4/MyD88/NF-κB axis was a possible mechanism of PCSK9 regulation of macrophage polarization. Conclusion. Our data suggested that PCSK9 modulated macrophage polarization-mediated ventricular remodeling after myocardial infarction.